Impact of Deep Breathing and Massage on Pain Reduction in Herniotomy Patients - Setiyaningsih, Yunnita (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2024)
Herniotomyis a surgery performed to free the hernia sac up to the neck, so that adhesions do not occur and then it is repositioned. The hernia sac is stitched, tied as high as possible and then cut. The patient will always experience pain after surgery on day 1. Deep breathing and massage relaxation techniques are one of the non-pharmacological pain management methods to reduce pain. this research aims todetermine the effect of deep breathing relaxation techniques and massage on reducing the pain scale in herniotomy patients. This research uses a literature review by searching articles on the Google Scholar electronic database. Several articles were found in the Google Scholar search database, but only 8 articles met all the inclusion criteria and were reviewed. Results: pain in post-operative patients often occurs, there are many non-pharmacological techniques to treat pain, one of which is the deep breathing technique. Conclusion: The conclusion of the 8 journals studied is that deep breathing relaxation therapy is very influential in reducing pain intensity in postoperative patients if done correctly and continuously.